“Diseño de un sistema de gestión de inventarios para el control de materias primas e insumos en la fábrica de productos lácteos Guerrero”. - Camacho Reyes., Angel Gabriel (2021)
The purpose of this research study was to design an inventory management system at ‘Productos Lácteos Guerrero’ Factory, to control the optimal requirements of raw materials and supplies that satisfy the expected demand. The research is descriptive; the inductive and synthetic-analytical as well as techniques such as field observation and documentary review to gather information, and the instruments were proposed according to the specific objectives. The system design started from an analysis in the current management process and the problem that contribute to the non-compliance of the expected demand of the three study families (cheese, yogurt and milk delicacy) was identified, later the methodological proposal was established to comply with the system. For this, the optional replenishment model was applied (hybrid model s, S), which allowed determining the target inventory, safety stock and review period; the information used in the development of the raw material requirements planning (MRP). In addition, a reorganization and control model was proposed through the application of ABC analysis that allowed the distribution of raw materials and supplies with the criterion of use and value; moreover, management procedures were standardized by using flow charts and appropriate formats to ensure traceability within the process. Finally, the current system was contrasted with the one proposed to demonstrate the improvement that the company will obtain when implementing the project, results measured with indicators such as waste and increase in gross profit and reduction in management costs. With the implementation of the research study, the impacts that would be generated are technical because it will be possible to improve the management process; social because it will increase the level of service and provide stability to human resources (internal staff) and economic because it will take advantage of the gross profit, they do not generate costs for shortages and it will reduce the costs associated with the process. Based on the results obtained, it is concluded that the tools used in the design of the management system made it possible to maintain adequate planning and stock control to meet demand and take advantage of gross profit, in the same way, it contributed to the optimization of the costs involved (ordering costs and holding costs).